Preliminary observations on indigenous knowledge and the uses of natural resources in Banting and Padawan - Eva Kristin Larry Sait,; Neilson Ilan Mersat,; Wong, Swee Kiong (Penerbit Universiti Kebangsaan Malaysia, 2018)
This paper discusses preliminary findings of the study on indigenous knowledge of various cultural, religious, medicinal and culinary uses of the natural resources found in two different indigenous communities in Sarawak, namely the Iban of Banting and the Bidayuh of Padawan. Structured interviews were carried out with each household head in the selected villages to determine indigenous knowledge of these communities on the usage of and reliance on natural resources. Through focus group discussions, indigenous knowledge on the various uses of identified natural resources is still available in these two communities. Their dependence on natural resources as building materials, food and, in the economic aspects still exist. However, their dependence on natural resource is diminishing. The indigenous knowledge gap between the old and younger generation of both Iban dan Bidayuh areas has also been identified. Most of the young people are no longer practicing traditional way of life because they are more comfortable with the modern way of life today. In addition, most Iban people in Banting, and the Bidayuh in Padawan have embraced Christianity and practiced modern way of life.